Coronavirus disease 2019 (COVID-19). First part: Introduction - Valdivieso-Rodriguez, Manuel (2021)
Several articles prepared by distinguished Peruvian doctors based in the United States in relation to the global pandemic of Coronavirus Disease 2019 (COVID-19) are presented. The articles were based on presentations made by these scientists as part of the educational program of the XLVII Annual Convention of the Peruvian American Medical Society (PAMS) that this year was made virtually because the pandemic made it impossible for us do it in person in Arequipa, Perú. The virtual presentations took place on september 17 and 18, 2020 and were made via Zoom. These short and precise virtual conferences were made possible by the co-sponsorship of PAMS, the Universidad Peruana Cayetano Heredia in Lima, Peru and the Universidad Católica Santa Maria in Arequipa, Peru.